A Rare Odontogenic Cyst: Gingival Cyst of the Adult. A Case Report and Review of the Literature in Elderly Patients - Martina Frigerio; Rami Al Eid; Tommaso Lombardi (Hindawi Limited, 2023)
Gingival cysts of adults (GCAs) are a relatively rare type of odontogenic cysts developing from the remnants of the dental lamina. Although GCAs generally affect individuals below the age of 65, their findings in older patients may exceptionally occur. Usually asymptomatic, they present as small, generally solitary nodules, located on the attached gingiva, primarily in the mandibular canine and premolar regions. This report highlights a rare case of a solitary GCA in an 82-year-old patient, who presented with a discrete nodule located between the right mandibular canine and first premolar. An excisional biopsy was performed, and the diagnosis of GCA was confirmed by the histological examination. No recurrence was observed during the 18-month follow-up period. Additionally, a literature review was conducted to analyse the clinical and pathological characteristics of GCAs in patients aged 65 and older. By providing details of this rare entity, our case study highlights the importance of considering GCAs when diagnosing gingival lesions in geriatric patients. By increasing our understanding of GCAs in the elderly population, our findings can help improve diagnosis as well as management strategies for these lesions.